Elmo's big lift-and-look book - Ross, Anna; Mathieu, Joseph P. (New York : Random House, 1994)
Presents a lift-the-flap board book that introduces early readers to numbers, shapes, letters, opposites, and simple objects.
On board pages.
At head of title: 123 Sesame Street.
"Featuring Jim Henson's Sesame Street Muppets"--Cover.
Keywords: Toy and movable books -- Specimens